The Rationale for Probiotics Improving Reproductive Health and Pregnancy Outcome. (18th February 2013) - Reid, Jennifer N. S.; Bisanz, Jordan E.; Monachese, Marc; Burton, Jeremy P.; Reid, Gregor
Abstract : Problem: Medical problems of most importance to reproductive health of women differ to some extent between the developed world and resource‐disadvantaged countries. Nevertheless, many share a common link in microbial involvement. Method of study: A review of the peer‐reviewed literature on microbiota, probiotics, and reproductive health. Results: Indigenous and probiotic lactobacilli express properties antagonistic to pathogens, but complementary to host immunity. These organisms are associated with conception, reducing the risk of infection, as well as potentially lowering the risk of a number of complications of pregnancy that otherwise lead to maternal and infant mortality and morbidity. Conclusions: The ability to manipulate the microbiome and to improve immunity through probiotics holds much promise. The lack of improvements over the past 40 years in managing urogenital infections in women is incomprehensible. Support for innovative diagnostic and treatment options is needed, including testing and implementing probiotic therapies, especially for women with poor access to healthcare and good nutrition.